Ukraine: The New Reforms and Internationalization - Knutson, Sonja; Kushnarenko, Valentyna (International Higher Education, 2015)
The progress of internationalization in higher education in the Ukraine continues to be challenged by tensions and instability created by escalating hostilities with Russia. However, a new Law on Higher Education, adopted on July 31, 2014, proposes coherent strategies to optimize university autonomy, provides frameworks for effective oversight, promises to intensify local university research and brings transformative innovations to current university approaches to internationalization. This paper highlights some of the law’s major reforms which can positively impact internationalization along with potential pitfalls related to successful implementation.